Cost estimates of diarrhea hospitalizations among children <5 years old in Zimbabwe. Issue 43 (7th October 2020) - Mujuru, Hilda A; Burnett, Eleanor; Nathoo, Kusum J; Ticklay, Ismail; Gonah, Nhamo A; Mukaratirwa, Arnold; Berejena, Chipo; Manangazira, Portia; Rupfutse, Maxwell; Chavers, Tyler; Weldegebriel, Goitom G.; Mwenda, Jason M.; et al.
Abstract: Introduction: Diarrhoea is a leading killer of children <5 years old, accounting for 480, 000 deaths in 2017. Zimbabwe introduced Rotarix into its vaccination program in 2014. In this evaluation, we estimate direct medical, direct non-medical, and indirect costs attributable to a diarrhea hospitalization in Zimbabwe after rotavirus vaccine introduction. Methods: Children <5 years old admitted to Harare Central Hospital from June 2018 to April 2019 with acute watery diarrhea were eligible for this evaluation. A 3-part structured questionnaire was used to collect data by interview from the child's family and by review of the medical record. A stool specimen was also collected and tested for rotavirus. Direct medical costs were the sum of medications, consumables, diagnostic tests, and service delivery costs. Direct non-medical costs were the sum of transportation, meals and lodging for caregivers. Indirect costs are the lost income for household members. Results: A total of 202 children were enrolled with a median age of 12 months (IQR: 7–21) and 48 (24%) had malnutrition. Children were sick for a median of 2 days and most had received outpatient medical care prior to admission. The median monthly household income was higher for well-nourished children compared to malnourished children (p < 0.001). The median total cost of a diarrhea illness resulting in hospitalization was 293.74 (IQR: 188.42, 427.89). Direct medical costs, with a median of 251.74 (IQR: 155.42, 390.96), comprised the majority of the total cost. Among children who tested positive for rotavirus, the median total illness cost was 243.78 (IQR: 160.92, 323.84). The median direct medical costs were higher for malnourished than well-nourished children (p < 0.001). Conclusion: Direct medical costs are the primary determinant of diarrhea illness costs in Zimbabwe. The descriptive findings from this evaluation are an important first step in calculating the cost effectiveness of rotavirus vaccine.